High vs. low vancomycin therapeutic concentrations in periprosthetic joint infection: A retrospective cohort analysis - Cheng, Jingdong; Wang, Dehua; Chen, Yanqing; Zhao, Qingqing; Ou, Qianyi; Zhang, Liangming; Li, Xinyu (Frontiers in Pharmacology, 2025)
ObjectiveCurrent guidelines recommend vancomycin concentrations of 10–20 μg/mL for most infections, with higher levels (15–20 μg/mL) suggested for severe cases. However, evidence supporting these recommendations in periprosthetic joint infection (PJI) is limited. This study aims to evaluate the impact of different vancomycin concentration ranges (10–15 vs. 15–20 μg/mL) on the safety and effectiveness in PJI population.MethodsThis retrospective study included 37 patients with vancomycin Therapeutic Drug Monitoring due to periprosthetic joint infection. Patients were categorized into two groups according to vancomycin concentrations, low concentration group (10–15 μg/mL) and high concentration group (15–20 μg/mL). Patients were followed up for at least 2 years. The long term clinical outcomes, inflammatory markers, as well as adverse events were compared. A physiologically based pharmacokinetic model was established to compare vancomycin distribution in kidney and bone marrow between the two groups.ResultsThere were 23 (62.16%) patients classified as the HC group and 14 (37.84%) as the LC group. The average steady-state trough concentration (Css) in the HC group was 17.74 μg/mL, and in the LC group was 12.11 μg/mL. At the end of follow-up, two patients (5.40%) in the HC group had died, and one (2.7%) was readmitted for joint fusion due to recurrent infections, whereas no deaths or readmissions occurred in the LC group. However, no significant differences were identified. Similar improvements from baseline were observed across WOMAC, Harris, HSS, and SF-12 scores between the groups. The synovial white blood cell (WBC) count was significantly lower in the HC group compared to the LC group (5,481 vs. 7,106/μL, P = 0.009), with a more pronounced reduction from baseline noted. The PBPK model showed a greater increase in drug distribution to the bone marrow in the HC group (20.66 μg/mL vs. 14.34 μg/mL), with a smaller rise in the kidney (376.2 μg/mL vs. 327.7 μg/mL).ConclusionMaintaining vancomycin concentrations of 15–20 μg/mL is associated with better infection control for PJI patients who present with higher synovial WBC account, without compromising patient safety, joint function, or long-term quality of life.